ANALISIS STRUCTURAL EQUATION MODELING KINERJA SISTEM INFORMASI DAN DATA IMUNISASI BALI TINGKAT PUSKESMAS DENGAN MODEL DELONE DAN MCLEAN TAHUN 2020 - Yoga, I Made Esa Sadana; Widarsa, I Ketut Tangking (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 1 (2021): April 2021, 2021)
ABSTRACT Immunization Information and Data System (SIDI) Bali has been implemented since early 2019 as a primary and mandatory immunization cohort register, but there are still many problems encountered in its implementation. This study aims to determine the factors that influence user satisfaction and the net benefits of SIDI Bali at public health center level. A cross-sectional study was conducted on all immunization officers at public health centers in Bali totaling 114 respondents. The study was conducted from March to June 2020. All datas were collected using a questionnaire that had been tested for validity and reliability. The data analyzed using Structural Equation Modeling (SEM). The results of the study based on SEM analysis stated that the factors that significantly influenced user satisfaction were information quality and service quality with a total effect of 0.326 and 0.241, respectively. Factors that significantly affected net benefits were information quality (0.379), service quality (0.337) and user satisfaction (0.667).Efforts that can be made are to improve quality in various aspects by completing the system output format, increasing the accuracy and relevance of data, implementing children's NIK, having supervisors and special teams in each region to respond the problems, and create work modules and modules addressing problems as anticipate if there is a change of officer. Keywords: Information System, DeLone and McLean, SEM